The Design of Smart Prototype Pet Feeder Using Passive InfaRed (PIR) Sensors - Marlina, Erni (Information Technology and Science (ITScience), 2023)
Food is necessary to support daily life and in pets like cats. Pet feeders are usually carried out routinely by pet owners by taking the time to stay at home and feed the pets. With activities requiring animal owners to be outside the home for long periods, it is necessary to design a prototype that can automatically assist the process of providing food, especially dry food, to pets. So pet feeders can be carried out even though the owner is not at home and does not have spare time. The system was built using the C language related to the Code Vision tools that support the hex file compiler into the microcontroller. The research method used is the experimental method, namely conducting trials (trial and error) directly on the research object and the comparative testing method for testing the built system. The auto pet feeder prototype uses the ATMega8535 IC by utilizing a PIR (Passive InfraRed) sensor to detect movement around the animal bowl. The PIR sensor detects well as expected, and it has an effective detection range of up to 5 meters. Not only detects humans, but the PIR sensor can also detect other living things. The PIR sensor will send a signal to the microcontroller to open the valve from the food measuring station, which is driven by a DC motor based on the detected motion to drop food into the animal's bowl. PhotoDioda controls the amount of food falling into the animal's bowl. The test results of this tool show that at a distance of 0–6 meters, the PIR sensor can provide feedback or detect animal movements well.